Provenance and tectonic setting of the protoliths of the Metamorphic Complexes of Sierra de San Luis - López de Luchi, M.G. (2003)
A major and trace element based characterization of the metasedimentary protoliths of three metamorphic units of Sierra de San Luis (Pringles Metamorphic Complex, San Luis Formation and Conlara Metamorphic Complex) is presented. Geochemistry indicates a dominance of shales in the protoliths of San Luis Formation, whereas greywackes and shales made up the Conlara Metamorphic complex and mainly greywackes, the Pringles Metamorphic Complex. Both major element data and trace element ratios (i.e. Th/Sc, Th/U,) indicate a source with an average upper crustal composition for the protoliths of the Pringles Metamorphic Complex, the San Luis Formation and the shales of the Conlara Metamorphic complex. A component with less evolved signature may be inferred for the metagreywackes of the Conlara metamorphic Complex. Mixed sourced detritus are indicated for the three units with clastic material resulting mainly from both andesitic and acidic/recycled detritus. The overall data consistently suggest a continental island arc and/or active margin setting as the more probable geodynamic scenario for the deposition of the sedimentary precursors of the studied units. In this context, a back-arc setting can account for the mixed nature of the inferred source areas with uplifted old basement and arc-related detritus as the end members of the mixtures. The inferred back-arc basin would have evolved through the Cambrian receiving the sediments derived from the Pampean Orogen to the east combined with probably some old crust exposures and to the west the source might have been controlled by the active continental margin. © 2003 Asociación Geológica Argentina.